Analisis Implementasi Akad MMQ Pada BMT Sebagai Alternatif Pembiayaan Syariah Mikro - Permana, Deni; Suparni, Suparni; Momy, Momy Damayanti (TAFAQQUH, 2025)
This study analyzes the implementation of the Musyarakah Mutanaqisah (MMQ) contract at BMT Amanah Berkah Mandiri in Bandung City as an alternative model for Islamic microfinance. Using a qualitative case study approach, data were collected through in-depth interviews with 8 informants (1 financing manager, 2 operational staff, 5 business partners), three months of field observation, and document review. Findings reveal that MMQ is implemented through five stages: feasibility assessment, joint capital agreement (BMT 70%, partner 30%), business operation, gradual ownership reduction over 24–36 months, and full ownership transfer. Key challenges include low Islamic financial literacy among partners (4 out of 5 did not understand the mutanaqisah mechanism prior to education), limited initial capital at the BMT, and the absence of standardized operational procedures. Nevertheless, MMQ proves more equitable than murabahah by applying proportional profit-sharing and fostering partner independence. This study contributes a practical framework for MMQ implementation in Islamic microfinance institutions. Limitations include a single-site design and restricted access to detailed financial data.